Human Microbiome - Beloborodova, Natalia V.; Grechko, Andrey V. (Biochemistry, 2021)
The book is mainly of interest to researchers in the field of the human microbiome. A lot of new useful knowledge can also be learned from this book by doctors who use scientific achievements for diagnosis and treatment, as well as postgraduate students who participate in research projects on the role of microbiota in pathophysiological processes. This book reflects current data on both methods of studying the microbiota and methods of its correction. Special attention is paid to the role of the microbiota in diseases such as stroke, cancer, autism, allergies, psoriasis, colitis, liver diseases, etc.; the mechanisms of interaction of the microbiota with drugs and natural products are considered. The scientific editors were happy to work on this book and hope that it will be useful to readers.